Agribusiness Performance through Innovation: The Case of Arabica Bemba Coffee in Enrekang - Indria Khairina; Muhammad Rusdi; Bahtiar Herman (Hasanuddin Economics and Business Review, 2026)
This study examines how innovation capability and market orientation influence agribusiness performance through post-harvest process innovation in the case of Bemba Arabica in Enrekang. A quantitative-explanatory design using PLS-SEM was employed with 80 multi-source respondents (farmers/groups, operators/QC, managers/marketing, B2B buyers). A Likert-type 1–5 instrument was tested for reliability and validity; a structural model assessed direct, indirect, and total effects. Results indicate innovation capability and market orientation have a significant positive effect on process innovation; process innovation has a significant positive effect on agribusiness performance. The direct effect of innovation capability on performance is small but significant, while the direct effect of market orientation on performance is insignificant indicating a dominant mediating role of process innovation. Findings confirm that standardized SOPs for fermentation–drying, QC/cupping, and traceability are the primary pathways for converting “market voice” and innovation capability into economic value. Practical implications include prioritizing standardization across suppliers, strengthening measurement/experimentation capacity, and managing structured market feedback.